2015
DOI: 10.1002/ppap.201400215
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Parameter Aspects in the Fabrication of Stable Amine Functionalized Plasma Polymer Films

Abstract: Amine containing plasma polymer films are of interest due to their ability to bind biomolecules either covalently or electrostatically. One issue with generating such plasma polymers is the need to generate sufficient amine density on the surface to enable binding, while simultaneously maintaining the chemical, physical stability of the surface in aqueous media. Here we investigate the relationship between plasma parameters, film stability for two commonly used monomers, allylamine AA, ethylenediamine EDA. Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…EDA showed a significant increase in the silicon signal, particularly at high primary amine concentrations. This is consistent with previous measurements using the current reactor, although at a higher pressure, 25 which showed that EDA films were unstable except at high power. Indeed, from the data it is likely that the EDA films at low power were almost completely dissolved.…”
Section: Stabilitysupporting
confidence: 93%
“…EDA showed a significant increase in the silicon signal, particularly at high primary amine concentrations. This is consistent with previous measurements using the current reactor, although at a higher pressure, 25 which showed that EDA films were unstable except at high power. Indeed, from the data it is likely that the EDA films at low power were almost completely dissolved.…”
Section: Stabilitysupporting
confidence: 93%
“…The plasma processing of materials including the amine plasma polymerization has gained considerable popularity for the development of bioactive materials, biosensors, antibacterial, and anti‐fungal surfaces . Various processes, monomers, and plasma reactors were employed to obtain the desired properties of the layers and several reviews reported the most prominent results achieved using allylamine, heptylamine, ethylenediamine, NH 3 , NH 3 /C 2 H 4 , and NH 3 /C 2 H 2 plasma polymerizations. However, several drawbacks were noticed for these methods as well.…”
Section: Introductionmentioning
confidence: 99%
“…The plasma coating also has to maintain its mechanical integrity since premature delamination or cracking will lessen its benefit. Stability of plasma coatings for biomedical applications has been widely studied through immersing specimens in water or phosphate buffered saline for a certain period of time [3639]. In this paper, we report on the chemical stability of plasma nanocoatings after prolonged immersion in a simulated body fluid (SBF) at 37 °C.…”
Section: Introductionmentioning
confidence: 99%